Constructing a Pedagogy of Apparentness - Tramantano, Adam (Art/Research International, 2022)
In this explorative essay, I discuss the complexity of apparentness as it pertains to being a teacher educator and an artist. Notions from creative and postmodern research approaches help me suggest that it is a quality of perception and not a quality of art or any other kind of text. In this exploration of how apparentness comes in and out of focus for me as an educator and as an artist, I begin with a discussion of the role of art in my becoming a teacher educator; I realize art’s efficacy as a site for exploring the acts of facilitating discussions, drawing the attention of others, and raising an awareness for what we believe matters. As a painter, I reflect on and inquire into what is laudable and limited in these forays of connecting art to teaching and education. The research approach is narrative and reflective, not intent on the discovery of discreet findings, but more interested in discovering questions and in offering some ways of framing my experiences and their possible implications for educators, teacher education, art, and artists. I ponder the parallels between art and education, particularly in how viewing art can be a metaphor for classroom discussions. The essay is concerned with what we believe is apparent and mysterious, and how we engage in dialogue with the resonance and dissonance of the perceptions of others.